Analisis Pengaruh Inklusi Keuangan, Inflasi, dan GDP per Kapita terhadap Stabilitas Sistem Keuangan di Negara Berkembang Asia Pasifik - Sri Wahyuningtyas (Diponegoro Journal of Economics, 2021)
Financial inclusion has an important role in financial system stability. Limited access to financial srvices is an obstacl for the community to access formal financial institutions so that financial inclusion is needed to realize a financial system that is more efficient and accessible to the public. This study aims to analyz the effect of financial inclusion, inflation and GDP per Capita on financial system stability in developing Asia Pacific countries. This study uses quantitative descriptive analysis, where descriptive analysis describes the conditions of financial inclusion in each country using the Financial Inclusion Index. In the quantitative analysis, panel data regression method will be used using the FEM model. The results of the analysis show that both financial inclusion and inflation have a significant positive effect on financial system stability, while GDP per Capita has no effect on financial system stability.